THE EFFECT OF OPERATING CASH FLOW AND NET PROFIT ON STOCK PRICES IN HEALTHCARE SECTOR COMPANIES - Linda Lihar Dhini; Ninuk Riesmiyantiningtias; Woro Dwi Hartanty (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This study aims to analyze and empirically examine the of operating cash flow and net profit on stock prices in healthcare sector companies listed on the Indonesia Stock Exchange during the period from 2021 to 2023. The research employs a descriptive quantitative method, with data collected from the financial statements of healthcare sector companies and stock price reports (using year-end closing prices) listed on the IDX for the 2021–2023 period. The sample in this study was selected using a purposive sampling method. The data were analyzed using multiple linear regression, and the data processing was conducted using SPSS version 30. The population in this study includes all healthcare sector companies listed on the IDX during the 2021–2023 period. The results of the study indicate that, partially, operating cash flow does not have a positive and significant effect on stock prices. In contrast, net profit has a positive and significant effect on stock prices. Simultaneously, both operating cash flow and net profit have a positive and significant effect on stock prices of healthcare sector companies listed on the Indonesia Stock Exchange during the 2021–2023 period.